In vivo evaluation of arsenic-associated behavioral and biochemical alterations in F0 and F1 mice. (April 2020) - Biswas, Sheta; Banna, Hasan Ul; Jahan, Momotaj; Anjum, Adiba; Siddique, Abu Eabrahim; Roy, Apurba; Nikkon, Farjana; Salam, Kazi Abdus; Haque, Azizul; Himeno, Seiichiro; Hossain, Khaled; Saud, Zahangir Alam
Abstract: Groundwater contaminated with arsenic (As) is the biggest threat to public health in Bangladesh. The children of As-exposure parents are also exposing to As through drinking water. The effects of As on the children's health of As-exposure parents are poorly understood. An animal study was taken to evaluate the effects of As on behavioral and biochemical changes in F1 mice. Swiss albino mice were separated into three groups: a) control, b) As-treated F0 and c) As-treated F1 . Elevated plus maze and Morris water maze tests were used for evaluating anxiety, spatial memory and learning, respectively. We found that the effect of As on anxiety like behavior, spatial memory and learning impairment in As-treated F1 mice was significantly higher than that of As-treated F0 mice and control group. Additionally, we also evaluated the effects of As on biochemical parameters by measuring ALT, AST, ALP, BChE, SOD activities and the level of creatinine in As-induced mice, where we found that all of the blood parameters were significantly changed in F1 generation. A significant portion of As accumulated in the brain, liver and kidney of F1 mice than F0 mice. Histological analysis revealed a significant change in tissue damage related to hepatic and renal dysfunctions that might be associated with As-induced biochemical alterations. In conclusion, arsenic plays an important role for the development of As-associated neurological disorders, hepatic toxicities, and renal dysfunctions in both F0 and F1 generations. Notably F1 mice were much more vulnerable to As-exposure than F0 mice. Highlights: Arsenic induces neurobehavioral and biochemical alterations in both F0 and F1 mice. Effects of arsenic are more pronounced in arsenic-exposed F1 mice than F0 . Accumulation of arsenic is higher in the liver, brain, and kidney of F1 mice. Arsenic markedly increases arsenic-associated tissue damages in the liver and kidney of F1 mice. Arsenic-exposed offspring mice are more vulnerable to arsenic exposure.